Factor Affecting of BIM Technique in the Construction Firms in Iraq - Hamada, Hussein M.; Ahmad Tarmizi, Haron; Zahrizan, Zakaria; Humada, Ali Mahmood (EDP Sciences, 2017)
The construction industry in Iraq became much more difficult than before because of complexities in the diagrams and documentations in the construction projects. Building information modeling (BIM) started to appear with entry the foreign companies to build the large projects in Iraq. It is a bode well technique for the construction industry, it has many benefits in all project phases from planning and scheduling to operation and demolition phase. This paper concentrated on the implementation of BIM technology and identify the benefits desired and challenges that reduce adoption this technique in the Iraqi construction industry. A qualitative approach has been used to collect data from two experts in the construction field in Iraq to show the factors affected on using BIM in the Iraqi construction firms. The results indicate to a rare implementation of BIM technology among construction professionals in Iraq. The study recommended encouraging the investment in the Iraqi construction markets to share the knowledge and experiences related to BIM technology between the construction professionals.